Relations between the comprehension of connectives and school performance in primary school. (August 2021) - Volodina, Anna; Heppt, Birgit; Weinert, Sabine
Abstract: The comprehension of connectives, which still develops across primary school age, is an important facet of academic language proficiency. We investigated relations between the comprehension of connectives and school performance in primary school. Drawing on two cohorts with a total of 294 students and two measurement points either in Grades 2 and 3 (Cohort 1; n =  139) or in Grades 3 and 4 (Cohort 2; n =  155), we found positive effects of children's performance on a newly developed test on the comprehension of connectives on reading comprehension and mathematics one year later while considering, amongst others, the families' socioeconomic status, children's nonverbal cognitive abilities, and receptive grammar. Overall, data showed even more pronounced effects of the comprehension of connectives on test scores compared to school grades. Results are discussed with respect to the specific importance of the comprehension of connectives for school performance in primary school. Highlights: We used a new measure on the comprehension of connectives in primary school. Comprehension of connectives is related to test scores in reading and mathematics. Comprehension of connectives is related to students' school grades. Effects are more pronounced for test scores than for school grades. Effects are significant when potential control variables are considered.